Response of Nano Fertilizers and Varieties on Growth and Yield of Brinjal (Solanum melongena) - Sundar; Jay Narayan Tiwari; Harpal Singh; Gaurav Kumar Ahirwar; Sukpal; Iliyas; Poonam Yadav; Rahnuma Bano; Harsh Vardhan Singh Chauhan; Ajay Pratap Singh (Archives of Current Research International, 2025)
The experiment was conducted at Bundelkhand University’s organic research farm in Jhansi (U.P.) during the Rabi season of 2023-24. The site had favorable climatic conditions with an average annual temperature of 30.03°C and an annual precipitation of 871 mm. The experiment followed a Randomized Block Design (RBD) with three replications, involving three brinjal varieties (Hybrid Snow Ball, VNR-58, VNR-212) and nine treatments, including Urea, DAP, and Urea + DAP. Each plot measured 2.4×1.8 m with a gross experimental area of 370 m². Growth and yield parameters, including plant height, branches, leaves, fruit characteristics, and yield, were recorded. The results showed that Urea + DAP treatment consistently outperformed others across all growth and yield parameters. At 90 DAT, the Purple variety had the highest plant height (50.33 cm), number of leaves (73.91), and branches (17.02). The Urea + DAP treatment resulted in the largest fruit size and highest yield. The Purple variety showed the best fruit characteristics, including the largest fruit diameter (58.74 mm) and highest single fruit weight (105.76 g). Yields per plant were highest for the Purple variety (422.77 g) and Urea + DAP treatment (417.77 g).